“Obtención de aromas en granos de cacao ( Theobroma cacao L.) en el clon ccn51 a partir de pulpa de grutas en la provincia de mariscal cáceres” - Fasabi Vásquez, Katherine Deciré (2015)
The objective of this research was to improve and evaluate the sensory quality of cocoa beans (Theobroma cacao L) in the CCN51 clone in cocoa liquor, through the incorporation of fruit pulp during the fermentation process. Hourst after is the cocoa beans of the clone CCN51 with three different types of pulps: banana moquicho (Musa sp.), tangerine (Citrus nobilis), pineapple (Ananas sativus) the application made with three different relationships: 10:1, 10:2, 10:3; i.e. 10 kg of cocoa and (1, 2 and 3 kg) of fruit pulp. The process of fermentation was carried out for 168 hours, with the first mine to 48 hours and then every 24 hours. During this entire process is carried out by the physicochemical analysis every 12 hours determining soluble solids, pH, and porcentage of acidity both on the testa and cotyledon; likewise are performed the testa of court or physical analysis of dry grain and the sensory evaluation of cocoa liquor that was composed of 1 O panelists. The experimental design of the testa, was completely randomized, factorial arrangement in 3x3, with three replications per treatment. The results obtained, in the sensory analysis the relationship 10:2 banana moquicho obtained the highest score of 57.8 points, having this way in the majority of their attributes evaluated, the greater acceptability with the exception of the Smell which was 7. 12 points with the proportion 1O:1 Pineapple in the same attribute that obtained 7.15 points; at the same time the relationship 10:2 banana moquicho obtained a percentage of fermentation of 81 %, thus taking in this way an extra grain of quality according to Cortes (1994) cited by Sánchez (2007), who considered that the minimum percentage it is 80 %.